Digital Diplomacy In The Service Of Hegemony Policies The American President’s Tweets As An Example (Damascus University Journal of arts and humanities sciences, 2022)
This study seeks to use the qualitative and quantitative analysis of a sample of the American president’s tweets over the last three years (2016-2019) to reach the size and content of the increasing use of information and telecommunication technology، which is considered as the most important means of diplomacy in the current phase that could change the international diplomatic activity. This is applied on Donlad Trump’s overuse of Twitter in the (Digital) indirect diplomacy in the promotion of his administration’s policies and interference in other countries. His overuse of Twitter goes against the international laws and norms and blackmails his rivals and allies alike. This gives him a great deal of the freedom of expression and behavior which lies outside the traditional diplomatic framework، and offers him the chance to change his timely (tactic) policies، according to the magnitude and reaction of his tweets.
Keywords: diplomacy; digital; tweets; Trump; policies; hegemony